2007
DOI: 10.1073/pnas.0610548104
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Parkin in-between-ring domain provides insights for E3-ligase dysfunction in autosomal recessive Parkinson's disease

Abstract: Mutations in Parkin are one of the predominant hereditary factors found in patients suffering from autosomal recessive juvenile Parkinsonism. Parkin is a member of the E3 ubiquitin ligase family that is defined by a tripartite RING1-in-between-ring (IBR)-RING2 motif. In Parkin, the IBR domain has been shown to augment binding of the E2 proteins UbcH7 and UbcH8, and the subsequent ubiquitination of the proteins synphilin-1, Sept5, and SIM2. To facilitate our understanding of Parkin function, the solution struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 46 publications
3
79
1
Order By: Relevance
“…The second domain, known as IBR, typically has a C 6 HC signature and is present only in RBR proteins. Recent structural data have shown that the IBR domain in fact consists of two consecutive zinc-binding domains, respectively, based on C 4 and C 2 HC ligands (Beasley et al 2007). Finally, the third, C-terminal domain, often called RING2, resembles a RING finger (e.g., it also contains a C 3 HC 4 signature).…”
Section: Introductionmentioning
confidence: 99%
“…The second domain, known as IBR, typically has a C 6 HC signature and is present only in RBR proteins. Recent structural data have shown that the IBR domain in fact consists of two consecutive zinc-binding domains, respectively, based on C 4 and C 2 HC ligands (Beasley et al 2007). Finally, the third, C-terminal domain, often called RING2, resembles a RING finger (e.g., it also contains a C 3 HC 4 signature).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the only experimental evidence exists for the IBR domain that has been shown to coordinate two Zn 2ϩ ions (23). The RING2 domain of the RBR family member HHARI has been observed to coordinate only a single Zn 2ϩ ion, although it was originally thought to ligate two metal ions (36).…”
Section: Differential Stability Of Rat and Humanmentioning
confidence: 99%
“…A New Domain in Parkin Identified by V8 and Trypsin Limited Proteolysis-Sequence similarity and alignment methods have identified the N-terminal UblD (1-75) and C-terminal RBR domains (238 -465) in parkin, whereas the central UPD (76 -238) conforms to no known domain sequence or structural motif (22,46). However, to date only the UblD and IBR domains (23,38,39) of parkin have actually been purified and characterized by protein chemistry methods. The purification of parkin now allows a more comprehensive examination of the remaining domain architecture within this E3 ligase protein, possibly establishing new domains and/or refining theoretical boundaries.…”
Section: Differential Stability Of Rat and Humanmentioning
confidence: 99%
See 2 more Smart Citations